2015
DOI: 10.1007/s40333-015-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal association in Asteraceae plants growing in the arid lands of Saudi Arabia

Abstract: The present research was undertaken to explor the possibility of arbuscular mycorrhizal (AM) association with Asteraceae plants in the arid lands of Saudi Arabia (Al-Ghat, Buraydah, Thumamah and Huraymila). AM fungal colonization in the roots, spore numbers in the rhizosphere soil, fungal species diversity and correlation between AM properties and soil properties were determined. The highest colonization was in Conyza bonariensis (65%) from Al-Ghat, Anthemis cotula (52%) from Buraydah and C. bonariensis (53%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Before DNA extraction, the samples were sieved through a 2-mm mesh for thorough homogenization and to remove roots and plant detritus (Dong et al, 2013;Dhar et al, 2015). Genomic DNA was isolated from 1 to 1.25 g of mixed soil using the PowerSoil DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA).…”
Section: Dna Extraction Polymerase Chain Reaction (Pcr) Amplificatiomentioning
confidence: 99%
“…Before DNA extraction, the samples were sieved through a 2-mm mesh for thorough homogenization and to remove roots and plant detritus (Dong et al, 2013;Dhar et al, 2015). Genomic DNA was isolated from 1 to 1.25 g of mixed soil using the PowerSoil DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA).…”
Section: Dna Extraction Polymerase Chain Reaction (Pcr) Amplificatiomentioning
confidence: 99%
“…Anthemis cotula develops arbuscular mycorrhizal fungi (AMF) associations that promote its growth while simultaneously influencing local biodiversity (Shah et al , 2008, 2009; Dhar et al , 2015). Shah and Reshi (2007) found that AMF were commonly associated with A. cotula populations collected from 14 different sites across the Kashmir Valley, India.…”
Section: Biologymentioning
confidence: 99%
“…Flora in Saudi Arabia entails 2250 varieties that belong to132 families in addition to 837 general species inhabit sand dunes; and also 90 are considered as halophytes (a plant adapted to growing in saline soil); 75 are trees; and 12 are aquatic plants. Beyond these species, 40 are believed to be endemic ( Abuzinada et al, 2005 , Dhar et al, 2015 , Abd El-Salam and Elhakem, 2016 ). The natural rangelands in Saudi Arabia are estimated to cover nearly 170,000,000 ha which are equal to 76% of the total land area of Saudi Arabia, situated mostly within arid and hyper-arid regions ( Abuzinada et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%